The Students’ Interest in Learning Basket Ball in Class XI Students of SMKN 1 Tirtajaya Karawang - Dhika Bayu Mahardhika; Tedi Purbangkara (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine student interest in learning at SMKN 1 Tirtajaya Karawang. The approach used in this research is quantitative, with a survey method and research design using cross-sectional. The population in this study were all students of class XI SMKN 1 Tirtajaya Karawang, totaling 155 students. At the same time, the sample was taken in one class using a purposive sampling technique, obtained in class XI TKR 1 with as many as 40 students as the class that will be given a questionnaire about students' interest in learning. The data is processed using Microsoft Excel Software. The results of this study indicate that the level of student interest in learning basketball shows a percentage of learning interest of as much as 43% with suitable criteria. So, it can be concluded that the level of student interest in learning basketball can increase if the teacher can present the material well and pleasantly and provide teaching through games so that students do not feel bored when learning takes place.